Re: Ashley M. Hopkins, Ganessan Kichenadasse, Christos S. Karapetis, et al. Concomitant Proton Pump Inhibitor Use and Survival in Urothelial Carcinoma Treated with Atezolizumab. Clin Cancer Res. In press. https://doi.org/10.1158/1078-0432.CCR-20-1876 - Satoshi Funada; Takashi Yoshioka; Yan Luo (European Urology Oncology, 2020)
Purpose We showed previously that breast cancer patients with certain circadian rhythm genotypes have higher incidences of toxicity when treated with radiotherapy at different times of day. This opens the way to genetically-guided chronomodulation as a cost-effective way to reduce side-effects while preserving treatment efficacy. We aimed to test whether similar time-of-day effects are observed in prostate cancer. Experimental design The analysis used the multinational, prospective observational REQUITE prostate cancer cohort (n=1760). All patients received external beam radiotherapy and were followed for two years. Regression analyses were performed in patients with complete data including genotypes and radiotherapy fraction times (n=877). LASSO and logistic regression models incorporated genotypes of SNPs in circadian rhythm genes, time of radiotherapy and their interaction. Primary endpoints were late rectal bleeding and urinary incontinence. Results Multivariable models show a significant effect of genotype, time of treatment and an interaction between PER3 genotypes and time for both primary endpoints. The 44% of patients with rs696305 C/C genotype are predicted to reduce their risk of rectal bleeding from 11% when treated at 09:00 to 5% at 17:00. Similarly, the analysis predicts a significant reduction in risk of urinary incontinence from 15% to 5% by avoiding treatment in the middle of the day for patients heterozygous for rs172933 (36% of patients). Conclusions These results agree with the earlier findings in breast cancer radiotherapy patients. Interaction between genotype and time of treatment suggests groups of patients could reduce side-effects and improve quality-of-life through chronomodulation.